Coaching presence as the foundation for the working alliance in AI coaching - Gy Yoong Nam; Jinhee Choi (PLoS ONE, 2026)
Although Human Resources managers have integrated artificial intelligence (AI)-mediated coaching into their practice, the role of traditional coaching elements—especially coaching presence—within these interactions remains underexplored. To examine perceived differences in the working alliance in AI-mediated coaching, we conducted pre- and post-interviews with 15 Human Resources leaders from South Korean IT companies. Participants were categorized into three groups: Novice (no prior coaching experience), coaching-educated (completed formal coaching education without certification), and certified (completed both education and formal certification). Using reflexive thematic analysis, we explored how participants experienced emotional bond, goal agreement, and task assignment. Findings indicate that AI coaching effectively accelerates goal clarification and provides structured task suggestions, yet it does not generate a coaching presence. In its absence, interactions were described as transactional and emotionally unresponsive; relational engagement weakened, goal agreement was less co-constructed, and task intentions were weakly internalized. Experience level shaped evaluations: coaching-educated and certified participants identified relational deficits early and judged AI more critically, whereas novices initially valued efficiency but later reported a lack of partnership and motivation. These findings highlight a limitation for AI coaching—procedural assistance without relational depth struggles to sustain a transformative working alliance. The study contributes to AI-relevant coaching and offers practical insights for developing emotionally responsive AI coaching platforms, including empathic attunement features, adaptive conversational feedback, and hybrid human-AI models.